Keefektifan Metode Fun Learning Terhadap Pembentukan Karakter Disiplin Siswa Tema Cuaca Kelas III SD Negeri Palebon 03 Semarang - Rizka Putri Sabrina; Ferina Agustini; Asep Ardiyanto (STKIP Andi Matappa Pangkep, 2021)
During this pandemic, learning is less effective, moreover, more students are bored by doing online learning at home. Learning is experiencing a revolution in meaning from just receiving to experiencing, so that teaching activities that were previously giving become inviting. The goal to be achieved in this study is to determine the effectiveness of the fun learning method on the formation of the discipline character tema cuaca class III at SD Negeri Palebon 03 Semarang. This type of research is quantitative research in the form of a One-shot case study design. Sources of data in this study obtained through interviews, questionnaires, and documentation. The results of this study are based on a preliminary study of observations and interviews of teachers carrying out learning using only conventional and monotonous methods. Based on the results of this study, it can be conveyed that the fun learning method can be applied in the learning process and makes the level of student discipline character increase.